The effect of focused reappraisal strategies on emotional intensity - Karol J. WILD; Andrei R. COSTEA; Sebastian „ PINTEA; Bianca MACAVEI; Oana Cătălina FODOR; Adrian N. OPRE (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
The intensity of healthy positive emotions could determine our ability to savour our lives fully. Focused reappraisal strategies which are effective in reducing negative unhealthy emotions could also have the effect of down-regulating positive emotions. Objective: The aim of our study was to investigate the effect of the extensive use of reappraisal strategies on changes in overall levels of emotional intensity. Methods: Our sample consisted of 108 subjects. Based on our experimental design, images from NAPS were used as positive and negative emotional stimuli. The valence and arousal of the emotional responses were measured. The subjects’ responses were categorised on the basis of which of the eight focused reappraisal strategies they applied. We used Linear Regression in order to test our hypothesis. Results: Based on our data, we identify justification and humour as reappraisal strategies that can lead to a decrease in the valence of positive emotions, with acceptance having an effect on the arousal of both negative and positive emotions. Conclusions: Our results suggest that in order to decrease unhealthy negative emotion, without at the same time reducing our ability to savour our lives by also decreasing the level of positive emotions, optimum levels of justification, humour and acceptance, used as reappraisal strategies, are needed. Limitations and recommendation for future research regarding emotional self-regulation interventions are identified and discussed.